If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1p = 4 Solving 7 + -1p = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1p = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1p = 4 + -7 -1p = 4 + -7 Combine like terms: 4 + -7 = -3 -1p = -3 Divide each side by '-1'. p = 3 Simplifying p = 3
| 90*23=x | | 60=0.5x+32 | | 7/x-5=6 | | (b+3)(b^2+2b+1)=0 | | 5y^2+10y-48=0 | | 24+0.79=1.19x | | 9=4(-3)-3 | | -14(-10x-13)=1162 | | -24+7x=25 | | 2x22/7x25x3.5 | | 4x^6+11x^5-x^3+7x+7=0 | | 3x-6(6x+31)=12 | | 2*x=512 | | 1/10_=k/100 | | 3x-4+9x=10 | | 2x+y^2=36 | | (x+9)+(4x^2)=0 | | 5x+1=8x-32 | | 5/9x31/90 | | (f+g)(x)=(x+9)+(4x^2) | | 20+5x=10-8x | | 11.5=14t+20.6 | | 21x+3y=210 | | x^2=-192 | | 30x^3+26x^2+4x= | | x-1/3=12 | | 6x+3x=3x-x | | x/2-3-x≥1 | | 4/(-2-8i) | | 9a+10=64 | | 3x+4.8=12 | | 4(x-7)=6(x-9)+60 |